Incidentally identified genetic variants in arrhythmogenic right ventricular cardiomyopathy‐associated genes among children undergoing exome sequencing reflect healthy population variation - Andrew T. Headrick; Jill A. Rosenfeld; Yaping Yang; Hari Tunuguntla; Hugh D. Allen; Daniel J. Penny; Jeffrey J. Kim; Andrew P. Landstrom (Molecular Genetics & Genomic Medicine, 2019)
Abstract Background With expanding use of clinical whole exome sequencing (WES), genetic variants of uncertain significance are increasingly identified. As pathologic mutations in genes associated with arrhythmogenic right ventricular cardiomyopathy (ARVC) carry a risk of sudden death, determining the diagnostic relevance of incidentally identified variants associated with these genes is critical. Methods WES variants from a large, predominantly pediatric cohort (N = 7,066 probands) were obtained for nine ARVC‐associated genes (Baylor Miraca). For comparison, a control cohort was derived from the gnomAD database and an ARVC case cohort (N = 1,379 probands) was established from ARVC cases in the literature. Topologic mapping was performed and signal‐to‐noise analysis was conducted normalizing WES, or case variants, against control variant frequencies. Retrospective chart review was performed of WES cases evaluated clinically (Texas Children's Hospital). Results Incidentally identified variants occurred in 14% of WES referrals and localized to genes which were rare among ARVC cases yet similar to controls. Amino acid‐level signal‐to‐noise analysis of cases demonstrated “pathologic hotspots” localizing to critical domains of PKP2 and DSG2 while WES variants did not. PKP2 ARM7 and ARM8 domains and DSG2 N‐terminal cadherin‐repeat domains demonstrated high pathogenicity while normalized WES variant frequency was low. Review of clinical data available on WES referrals demonstrated none with evidence of ARVC among variant‐positive individuals. Conclusions Incidentally identified variants are common among pediatric WES testing with gene frequencies similar to “background” variants. Incidentally identified variants are unlikely to be pathologic.